The Historical and Literary Legacy of Iskandar Zulqarnain - Adib Kurniawan (Journal of Economics and Business UBS, 2024)
Iskandar Zulqarnain, often equated with Alexander the Great, is a multifaceted figure whose legacy transcends historical accounts to enter the realms of myth and literature. This study explores his historical significance, literary representations, and socio-cultural implications across various societies. Employing a comprehensive literature review and qualitative analysis of primary and secondary sources, the research highlights how Iskandar's narrative adapts to different cultural contexts, particularly in Islamic, Persian, and Western traditions. The findings indicate that Iskandar's duality as both a conqueror and a unifier has led to a rich tapestry of stories that influence cultural pride and identity. Furthermore, the literary legacy of Iskandar is intertwined with historical narratives, showcasing how his character has been romanticized over time. This exploration reveals the complexities of Iskandar's legacy, emphasizing its relevance in contemporary discussions about nationalism and cultural identity. Overall, the study contributes to understanding how historical figures are remembered and reinterpreted, reflecting broader societal values and aspirations